Development Plans for Employee Engagement in Banking Institution during the Covid-19 Pandemic - Nabila Dianisa; Rudy Bekti (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
This study aims to identify the factor of employee engagement and analyze the current condition of employee engagement. The author gains in scope and depth of understanding and collaboration by mixing both qualitative and quantitative methods. Primary data is gathered from the questionnaire and interview with some employees, while secondary data is obtained from the company's annual report, a private document, and related journals. In addition to validity and reliability testing, the data will also be analyzed using statistical techniques. Some approaches are also applicable for assessing employee engagement results, such as Grand Mean, Top Box, and Engagement Scores. The results of the interview support data analysis. The triangulation technique uses to combine both results of the questionnaire and interview. The triangulation helps to confirm the findings, enhance understanding, and increase the validity. Based on the analysis, the author found several factors such as culture, opportunity, quality of life, people, and rewards. The study's result can be used to recommend the company to improve engagement during the Covid-19 pandemic.